Polarography with non-mercury electrodes: A review - Švancara, Ivan; Mikysek, Tomáš; Sýs, Milan (My University, 2022)
This article reviews non-mercury configurations that have hitherto been reported in the literature as the working electrodes applicable in polarographic measurements. The individual types, namely gallium, liquid amalgams, dropping electrolyte, and carbon fluid electrodes, together with a carbon paste-based assembly or even solid disc electrodes with a periodically renewable surface, are presented, discussed, and critically assessed with respect to their potential employment in the present day’s electrochemistry and electroanalysis.
Polarografie s nertuťovými elektrodami: Přehled
Keywords: characterization and evaluation; non-mercury electrodes; polarography; review; charakterizace a hodnocení; nertuťové elektrody; polarografie; přehled